The Divergence of Al-Kisā'i’s Thought from Basrah: A Critical Analysis of the Emergence of Kufah’s Nahwu School - Husnaya, Ni'ma Royyin; Budi, Rahmat Dinni Haerul (Journal of Arabic Language Studies and Teaching, 2025)
This paper aims to discuss the methods, thoughts, and contributions of Al-Kisā'i in the development of Nahwu science, especially the Kufah madrasah. The method used in the research is a literature study. In contrast, the method used in data analysis is historical analysis, which is a study of a problem based on the context of the historical development of the study. In its development, Nahwu has passed through various discussions and given birth to its characteristics in each madrasa in Nahwu science. This development is inseparable from the thoughts of Nahwu figures who laid the foundations of the rules in Nahwu science. As one of the pioneers of the Kufah madrasah, Al-Kisā'i has several methods and thoughts that distinguish it from the madrasa that emerged earlier, namely the Basrah madrasah. The results showed that; Al-Kisā'i in developing his thoughts in the field of nahwu, namely by expanding the use of history, namely by opening the possibility of history from shi'ir, expanding the use of qiyas, namely by considering the importance of nahwu rules based on uncommon language rules, expanding the differences in principles developed by the Basrah school.